The prevalence of gestational diabetes in women of child bearing age belonging to K.P.K - Gul, Bushra; Mehboob, Saima; Qayuom, Sumaira; Daud, Muhammad (Khyber Journal of Medical Sciences, 2022)
Abstract: This study was conducted with an aim to determine the prevalence of GDM in pregnant women using standard OGTT as a screening tool presenting to the antenatal care. After approval from the hospital ethical and research committee this cross sectional study was conducted in the department of obstetrics and gynecology, Khyber Teaching Hospital, and it included patients recruited through non probability consecutive sampling, presenting to OPD. A total of 126 patients were included in the study, with 16 to 28 weeks gestation. Screening for GDM was done with a 2 hour 75 g, oral glucose tolerance test. Patients were advised to have unrestricted diet and physical activity and come in the morning with overnight fasting. They were given 75g oral glucose load, in the form of Galaxose-D dissolved in 250ml of tap. A sample of blood was drawn one hour after glucose ingestion and send to the laboratory for blood glucose estimation by glucose oxidase hexokinase method. Blood sugar was estimated at 1 hour, 2 hour and 3 hour intervals and the findings were recorded on a structured Performa. Results were analyzed using SPSS version 13.